Značilne točke trikotnika kot funkcije - Hvala, Bojan (Obzornik za matematiko in fiziko, 2014)
Clark Kimberling's Encyclopedia of triangle centers contains well over 5600 centers. In the article we explain Kimberling's definition of a triangle center and present some related curiosities.
Keywords: geometrija; trikotnik; značilne točke; polinomske značilne točke